Making Citizens: Brazilian Social Policy from Getúlio to Lula. Issue 3 (December 2014) - Hunter, Wendy
This article compares and contrasts two important phases of social incorporation in Brazil: (i) an early punctuated period that integrated formal sector workers and civil servants under President Getúlio Vargas (1930–1945) and (ii) a later more extended sequence that strived to include the informal sector poor, beginning with the military regime (1964–1985), gaining momentum with the 1988 Brazilian Constitution and the presidency of Fernando Henrique Cardoso (1995–2002), and continuing under President Luiz Inácio Lula da Silva (2003–2010). It captures the shift from a welfare state based on corporatist principles to one that comes closer to basic universalism. Whereas Vargas's incorporation project addressed workers as producers, later governments incurporated the informal poor as beneficiaries of public policy programs – including income support policies – in a more individualist and liberal fashion.